Studi Sikap Profesionalisme Mahasiswa AKuntansi, Mahasiswa Bisnis, dan Lulusan Akuntansi di Indonesia Terhadap Praktik Manajemen Laba dan Pelaporan Keuangan - Se Tin (Universitas Kristen Maranatha, 2002)
The purpose of the research is to investigate whether accounting education is successful at instilling in accounting students and professional accountants a sense of responsibility to financial statement users. To answer this question, this study investigates changes in the opinions of undergraduate accounting students regarding earnings management, the disclosure of sensitive information, the costs and benefits of financial disclosures, and the responsibilities of corporate managers. This study compares accounting students' responses with the responses of students in other business disciplines and also compares accounting students' responses who take jobs in public accounting with the responses of those who enter corporate accounting. The samples are accounting students and other business students in public and private university. Of the 800 questionnaires were distributed to the students and 200 questionnaires to the professional and corporate accountant, 858 questionnaires were returned and 729 data were used. Data is selected using random sampling. The data collection is performed using direct survey to the respondents. The statistic method used to test hypotheses is nonparametric test (Mann-Whitney test). The results are as follows: first, at the public university, senior accounting students became more strongly opposed to omitting required financial disclosures or purposely misstating financial information than junior accounting students, but at the private university, we find no differences between senior and junior accounting students; second, at the public and private university, no differences are detected between sophomore students planning to major in accounting and sophomore planning to major in other business disciplines; third, no significance differences are detected between senior accounting students and senior students in other business discipline; forth, professional accountants oppose eaming management more strongly than corporate accountants; fifth, when students entering private industry and public accounting, they oppose camings management more weakly than they were in the university.